2017
DOI: 10.1007/s11104-017-3540-2
|View full text |Cite
|
Sign up to set email alerts
|

In the land of plenty: catch crops trigger nitrogen uptake by soil microorganisms

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
(107 reference statements)
0
10
1
Order By: Relevance
“…While it can be hypothesized that (i) legume-based mixtures take up less nitrogen than non-legume-based mixtures and/or (ii) mixtures with nitrophilic Brassicaceae species take up more nitrogen, no significant changes in N were observed between the different cover crop mixtures (Supplementary Table S3). This is in contrast to In’t Zandt et al (2018) reporting an effect of cover crop mixture on nitrate contents in soil. Overall, our results suggest that frost and rolling but not glyphosate termination method can lead to increase of the total N in soil.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…While it can be hypothesized that (i) legume-based mixtures take up less nitrogen than non-legume-based mixtures and/or (ii) mixtures with nitrophilic Brassicaceae species take up more nitrogen, no significant changes in N were observed between the different cover crop mixtures (Supplementary Table S3). This is in contrast to In’t Zandt et al (2018) reporting an effect of cover crop mixture on nitrate contents in soil. Overall, our results suggest that frost and rolling but not glyphosate termination method can lead to increase of the total N in soil.…”
Section: Resultscontrasting
confidence: 98%
“…Such impact of the termination treatment on denitrifiers can be explained by the differential effects of termination treatments on total N (Figure 1A), with increased denitrifier abundance in treatments stimulating soil total N (i.e., rolling). Previous studies showed that cover crops could stimulate N-immobilization in the microbial biomass (In’t Zandt et al, 2018), which could have a detrimental effect on denitrifiers that are using inorganic N for respiration. Since an impact of glyphosate on soil microbial community has been reported in a recent meta-analysis (Nguyen et al, 2016), we cannot rule out a direct toxic effect on some microbial taxa involved in denitrification at our field site.…”
Section: Resultsmentioning
confidence: 99%
“…This possibly occurred due to increased overall fitness of the plant due to release from nutrient stress, and, consequently, an increase in tolerance to speciesspecific soil-borne pathogens. Simultaneously, competition between plants and soil micro-organisms may be less strong due to high nutrient availability (Schimel and Bennett 2004;Liu et al 2016;in 't Zandt et al 2018), further decreasing negative plant-soil feedback effects.…”
Section: Plant-soil Feedback and Nutrient Availabilitymentioning
confidence: 99%
“…Such consistent changes are expected to interact with plant growth and hence to affect plant-soil feedback driven community assembly processes (e.g., Ehrenfeld et al 2005;Luo et al 2017). However, the few studies testing nutrient availability yield mixed results (Manning et al 2008;Petermann et al 2008;Harrison and Bardgett 2010), introducing two contrasting theories on how nutrient addition affects plant-soil feedback strength and direction via microbial community composition shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen management is especially challenging due to its complex cycle involving various chemical forms, transformation processes and pathways of loss within agroecosystems as well as relatively high-crop demand. By taking up soil mineral nitrogen (SMN) within plant tissues and promoting immobilization (in 't Zandt et al ., 2018), cover crops function effectively to mitigate the risk of N losses during fallow seasons (Pantoja et al ., 2016). Therefore, cover crops can reduce nutrient leaching losses by 70% on average as described in a meta-analysis of 18 studies (Tonitto et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%